2011
DOI: 10.1177/1028315311426783
|View full text |Cite
|
Sign up to set email alerts
|

Educational Experiences Associated With International Students’ Learning, Development, and Positive Perceptions of Campus Climate

Abstract: This research project uses the constructive-developmental tradition, in the selfauthorship framework of intercultural maturity (King & Baxter Magolda, 2005), to examine the extent to which 12 specific educational experiences may be associated with international undergraduates' learning, development, and perception of campus climate. The study uses multiple regression analysis of a stratified random sample of international student respondents to the Global Perspective Inventory (GPI; n = 437). The results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 39 publications
5
56
1
2
Order By: Relevance
“…So, bottom universities need some time to achieve those goals. Another weakness lack of internationalization, as the studies focused on the preferences of international students and faculties showed, is also related with qualified faculties (Eder, Smith & Pitts, 2010;Petruzzellis & Romanazzi, 2010), geographical location of university (Soo & Elliott, 2010;Bodycott, 2009), the city, job prospects for alumni (Hilden, 2011;Kamal Basha, Sweeney, & Soutar, 2016) and the number of facilities in campus (Jon, 2013;Glass, 2012;Yusoff, 2012). Meeting those criteria to be preferred by international students may seem very hard for bottom universities for now but in the future, it is not impossible to achieve those goals.…”
Section: Discussionmentioning
confidence: 99%
“…So, bottom universities need some time to achieve those goals. Another weakness lack of internationalization, as the studies focused on the preferences of international students and faculties showed, is also related with qualified faculties (Eder, Smith & Pitts, 2010;Petruzzellis & Romanazzi, 2010), geographical location of university (Soo & Elliott, 2010;Bodycott, 2009), the city, job prospects for alumni (Hilden, 2011;Kamal Basha, Sweeney, & Soutar, 2016) and the number of facilities in campus (Jon, 2013;Glass, 2012;Yusoff, 2012). Meeting those criteria to be preferred by international students may seem very hard for bottom universities for now but in the future, it is not impossible to achieve those goals.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to investigate the relationship between international student satisfaction and various factors that include campus climate (Glass, 2011), ability to gain proficiency in the English language (Fass-Holmes & Vaugh, 2014), and engagement with host nationals (Glass & Westmont, 2014). Studies also indicate the benefits of institutional support to international students.…”
Section: Recommendations For Practice: An Ecological Approachmentioning
confidence: 99%
“…International students with cash to spend may bridge that financial gap (Joseph, 2012;WES Report, 2015). Glass (2012) suggests that international students who participate in leadership programs, community service, and campus-organized diversity discussions, interact with people from diverse cultural backgrounds, and take courses with materials on race and ethnicity report greater levels of learning and development. However, that study focused on learning outcomes rather than motivation factors leading international students to study in the U.S.…”
Section: Review Of Literaturementioning
confidence: 99%